If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -6x = 19 + 3x Solving 1 + -6x = 19 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + -6x + -3x = 19 + 3x + -3x Combine like terms: -6x + -3x = -9x 1 + -9x = 19 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + -9x = 19 + 0 1 + -9x = 19 Add '-1' to each side of the equation. 1 + -1 + -9x = 19 + -1 Combine like terms: 1 + -1 = 0 0 + -9x = 19 + -1 -9x = 19 + -1 Combine like terms: 19 + -1 = 18 -9x = 18 Divide each side by '-9'. x = -2 Simplifying x = -2
| 4x/27+8x | | 2(5z-1)-2(6-2z)=4 | | 3(2z-2)-3(5-3z)=3 | | 3y/4=0.6 | | 60-3(E-5)= | | -3x+8x^2+1=0 | | 3(r-4)=3 | | -2b=10-8.58 | | 5h+9=4h+1 | | 3L+22=9l-20 | | 6-3f=18 | | 1.4t-12=-0.6t | | 1.4t-12=4x+23 | | x^2-2bx+a^2=0 | | 500+45(5)=y | | 500+45x=y | | 0.4xsquared-40x+360=0 | | z^2+4iz+5=0 | | x+5y/x | | 3(x-7)-4(x+2)=20 | | (x+5y)/x | | 4x-1=64 | | 7/11=x/45 | | 5x+0.9= | | 7x+0.2= | | 1/3(7x-1)=1/4 | | 81=9a | | 182/7+(5*11)=9a | | 12+144+20+6/7+(5*11)=9a | | 401.28+.2x=x | | -2+128=10 | | 5x-7=2x+12 |